The dark side of avocados: a review of anthracnose and stem-end rot in postharvest fruit - Bernal, Valentina Valencia; Boeckman, Nathanial J.; Aćimović, Srđan G.; Khodadadi, Fatemeh (Frontiers in Microbiology, 2025)
Avocados are a key global fruit crop with rising international demand. However, postharvest diseases like anthracnose and stem-end rot (SER) can lead to significant economic losses, with incidence rates surpassing 30% in some regions. The latent nature of these infections complicates detection and management, affecting fruit quality and marketability. This review examines the pathogens behind these diseases, highlights advancements in detection technologies such as the use of biochemical and non-destructive methods and explores host-pathogen interactions through emerging omics approaches. We also evaluate the impact of preharvest practices on disease outcomes and current management strategies, including the growing potential of biological control agents, systemic resistance inducers, and natural product-based formulations as sustainable tools that complement synthetic fungicides. Finally, we highlight implications for fruit quality and consumer perception, along with critical research gaps, particularly the imbalance between anthracnose and SER studies in avocados, and outline future directions for improving postharvest disease control in avocados.